1998
DOI: 10.1093/qjmed/91.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate-based haemofiltration in the management of acute renal failure with lactic acidosis

Abstract: Continuous haemofiltration with lactate-based replacement fluid is widely used for the treatment of acute renal failure (ARF). In the presence of lactic acidosis, such treatment exacerbates rather than improves the clinical state. Continuous haemofiltration using a locally-prepared bicarbonate-based replacement fluid was performed in 200 patients over 7 years. All the patients had ARF with concomitant lactic acidosis, or demonstrated lactate intolerance after starting haemofiltration with lactate-based replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 1 publication
2
34
2
1
Order By: Relevance
“…However, there was no increase in blood pressure or reduction in pressor requirements. The administration of lactate-based solutions has been reported to lead to an increase in blood lactate [15], but in our study blood and ultrafiltrate lactate concentrations were not different between the groups. We found that base excess was more rapidly corrected with bicarbonate fluids compared to lactate.…”
Section: Discussioncontrasting
confidence: 83%
“…However, there was no increase in blood pressure or reduction in pressor requirements. The administration of lactate-based solutions has been reported to lead to an increase in blood lactate [15], but in our study blood and ultrafiltrate lactate concentrations were not different between the groups. We found that base excess was more rapidly corrected with bicarbonate fluids compared to lactate.…”
Section: Discussioncontrasting
confidence: 83%
“…Hilton et al [10] have shown that use of bicarbonatebased solutions is associated with improved hemodynamic stability although no difference was found by Thomas et al [11] comparing lactate-and bicarbonate-based solutions. A recently completed multicenter study in Germany has further shown that use of lactate-based substitution fluids is associated with reduced hemodynamic stability in comparison to bicarbonate-based solutions [16].…”
Section: Principles Of Acid-base and Electrolytes Management In Crrtmentioning
confidence: 98%
“…Almost all involve continuous RRT (CRRT). Early uncontrolled studies showed the feasibility of CRRT modalities in the treatment of patients with renal failure and lactic acidosis (45)(46)(47) and emphasized the metabolic advantage of bicarbonate-over lactatebuffered dialysate (46). A recent single-center observational cohort study of 116 patients with AKI and lactic acidosis showed that CRRT using bicarbonate-buffered fluids can reduce blood lactate levels and raise pH (48).…”
Section: What Is the Most Effective Treatment For The Patient?mentioning
confidence: 99%